O Fenómeno da Desorçamentação: Breves Considerações à Nomenclatura - Nunes, Pedro (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2009)
The present article analyzes the meaning and reach of the nomenelature desorçamentação (off-budget). It is a recently used neologism in the literature of economic sciences and, in special, the public finances, that has generated some controversy, resulting in interpretations and visions many different for the same phenomenon. Although the concept does not have translation for other languages, intends to understand and make an approach to its terminological similarity. The context is, in particularly, the State Budget.